2021
DOI: 10.26803/ijlter.20.12.6
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Mathematics Education during COVID-19: An Exploratory Study of Teaching Practices for Teachers in Simultaneous Virtual Classes

Abstract: The current study has aimed to identify the status of teaching mathematics in simultaneous virtual classes, in the light of the Covid 19 pandemic, by uncovering the teaching practices in the fields of lesson planning, teaching the new mathematical knowledge, classroom management, and raising the level of interaction, and that of evaluation. The descriptive approach was used in this study, and a random sample, which consisted of 385 mathematics teachers in the Qassim Education Department, was chosen during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 4 publications
1
11
0
1
Order By: Relevance
“…Results indicated that the intervention program has a strong effect on students' learning. This extends prior research which indicated that there was a functional relation between Direct Instruction and increased receptive language skills when investigating specific instructional methods with Direct Instruction programs (Aloufi et al ., 2021;Crowley et al, 2013;Konstantareas et al, 2010;Makowski et al, 2013;Maljaara et al, 2012). Students on the experimental group participated in the language form and the rate prescribed by the program.…”
Section: Discussionsupporting
confidence: 84%
“…Results indicated that the intervention program has a strong effect on students' learning. This extends prior research which indicated that there was a functional relation between Direct Instruction and increased receptive language skills when investigating specific instructional methods with Direct Instruction programs (Aloufi et al ., 2021;Crowley et al, 2013;Konstantareas et al, 2010;Makowski et al, 2013;Maljaara et al, 2012). Students on the experimental group participated in the language form and the rate prescribed by the program.…”
Section: Discussionsupporting
confidence: 84%
“…So practice, employ, and modify the learners' ideas, perceptions, and explanations for misunderstanding mathematical concepts. Thus understanding the concept makes mathematical topics more comprehensive and meaningful (Aloufi et al, 2021). Ben-hur (M., 2006) believes that Concept-Rich Instruction stimulates active constructive learning to acquire mathematical knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Penalaran merupakan bagian penting dari pemecahan masalah (Ismanto, et al, 2019). Peserta didik dapat memperdalam pengetahuan dan pemahamannya terhadap penalaran matematika guna mengembangkan, memperbaiki (Choi dan Kim, 2017) dan menggunakan prosesproses dalam belajar matematika (Aloufi, et al, 2021). Hal ini karena kemampuan inilah yang terutama digunakan peserta didik sewaktu dihadapkan pada masalah matematika yang harus diselesaikannya (Utami, et al, 2018).…”
Section: Pendahuluanunclassified